FIT BAR BRAND STRENGTHENING STRATEGY IN MARKET PLACE WITH VISUAL MARKETING TECHNIQUES - WAHYUNING CHUMAESON; FANNY HENDRO ARYO PUTRO; MUHAMMAD ABDUL AZIZ; TOPAN SETIAWAN (CV KULTURA DIGITAL MEDIA, 2024)
The purpose of this research is to describe how the corporate strategy of the fit bar brand snack food manufacturer strengthens the market with visual marketing techniques. This is interesting because this snack product is being talked about by diet and healthy food activists and millennial teenagers. Calorie-rich food has become a sexy product amidst the growing awareness of living a restful life by regulating calorie intake. The study was conducted by looking at various digital media platforms used by the product to advertise. The data is interpreted in such a way with a descriptive-narrative approach, by looking for certain highlights that are considered to have interesting visual constructions. The results of the study found how the relatively new product emphasized marketing techniques with a visual approach. Visual is a technique that is considered appropriate for imaging a product, by displaying various beautiful and attractive images. Planting memories in the consumer psychology area at the photographic memory level, with the first appearance sensed by the eye.